A model for phased evacuations for disasters with spatio-temporal randomness. Issue 5 (4th May 2019) - Li, Menghui; Xu, Jinliang; Li, Jin; Liu, Xingliang; Ru, Han; Sun, Chao
ABSTRACT: This research presents an operable zoning approach for phased evacuations adapted to disasters with spatio-temporal randomness. As a criterion for prioritizing evacuation order, evacuation risk is formulated by taking into consideration the estimated residual evacuation horizon associated with the characteristics of the disaster, the estimated time-dependent capacities of outbound lanes related to network supply, and the time-dependent evacuation demand of an evacuation unit. The modeling of the subzone determined for phased evacuation is based on rescue demand, the characteristics of the disaster, and network supply, and is labeled as a high-risk evacuation zone (HEZ). The range of HEZ features a time-evolving pattern in accordance with phased evacuation. The zone partition paradigm can be seamlessly applied to different types of disasters, especially those with high spatio-temporal randomness. It also provides a generalizable approach for subzone partitioning in phased evacuation by minimizing evacuation risk. The proposed approach is examined on numerical experiments through the road network of Xi'an, China, the results of which highlight its strength in increased adaptability to the dynamics of disaster impact and improved performance in evacuation operation.